On the Internet, with the Exploded Text - Jessamyn West (In the Library with the Lead Pipe, 2011)
Looking at print books from a writer’s first-person perspective I wrote a book in 2009 and 2010. It’s getting published this year (2011) sometime. Let me tell you about what it’s like writing a print book for a large trade publisher during the long leisurely sunset of print. It was different from what I thought [...]